Keeping international law international, a reflection on Anthea Roberts’ “is international law international?” - D. K. Labin; T. Potier (Московский журнал международного права, 2020)
INTRODUCTION. Occasionally a book appears which has a significant impact on the scholarly community. A fine example of this is the work considered here by the Australian international lawyer, Anthea Roberts. Until very recently, comparative studies on international law were rare. However, as international law further develops and widens, so special attention will need to be paid to ensure that international law students are, to a greater extent, taught the same material and in the same way. As municipal systems of law became more mature, so doctrine and jurisprudence began to diverge. International law has now entered such a phase in its development and, in this excellent book, Dr. Roberts asks a series of very important questions: exactly what is taking place, what are the factors that are driving these processes, is such to be welcomed, is it unstoppable and where do we go from here?MATERIALS AND METHODS. The article reflects on Anthea Roberts’ book “Is International Law International?” (Oxford, Oxford University Press, 2017). The authors of the article consider the contribution of the monograph to legal science, particularly with its interest in a revived Comparative International Law.RESEARCH RESULTS. The view of the authors of the article is that Anthea Roberts’ book is a work of profound significance, which will, hopefully, inspire additional research in the field of Comparative International Law in years to come.DISCUSSION AND CONCLUSIONS. Comparative International Law is a relatively neglected field in International Law. Without question, the international legal academy (from the elite law schools of the permanent members of the United Nations Security Council) emphasises different things both in its scholarly writings and pedagogy. This needs to be given greater attention, even if, at least for now, it cannot be entirely arrested; so that the much-feared fragmentation of international law into not only separate fields and standards, but also in terms of agreeing on its content and application, is minimised.